Animal research. A bioethical reflection - Franco, Ana Lúcia; Nogueira, Marianne Nicole M.; Kalatzis Sousa, Natália Guimarães; da Frota, Matheus Franco; Fernandes, Clemente Maia S.; da Costa Serra, Mônica (Acta Bioethica, 2014)
Animal models are an important tool in scientific research. It is known that this practice must be based on bioethical principles in order to impose limits about pain and suffering, or for inspecting proceedings and research site. This study has as aim to evaluate and present current legislation ruling animal research in Brazil, comparing it with other countries, as well as fostering bioethical reflection about this issue. For this, we present current Brazilian legislation and we have carried out international literature review and discussion. The articles were searched in PubMed data base, using the key words “bioethics” and “animal welfare”. Nineteen articles from 1997 to 2013 were included. It was concluded the evident contribution of animal research for scientific research in several fields. It is morally relevant for humans, as rational beings, to secure humane treatment to animals contributing to research. The safest way to follow this path is establishing clear norms and studies well designed, involving society for assigning ethical norms. Thus, animal welfare would be guarantee.